New Hydrophobic IOL Materials and Understanding the Science of Glistenings. (3rd October 2015) - Tetz, Manfred; Jorgensen, Matthew R.
Abstract: An introduction to the history of intraocular lenses (IOLs) is given, leading up to modern hydrophobic examples. The roles of hydrophobicity, hygroscopy, materials chemistry, and edge design are discussed in the context of IOLs. The four major types of IOL materials are compared in terms of their chemistry and biocompatibility. An example of a modern "hydrophobic" acrylic polymer with higher water content is discussed in detail.